النظام القانوني للحريات العامة في الجزائر - لبنى روابحية (My University, 2019)
Summary: From the point of view of the topic: the legal regime of public freedoms in Algerian legislation It turns out that there is a fundamental idea underlying our research. The legal and constitutional status of Algeria's public freedoms and the Algerian Constitution has ensured a balance between two things, The first is to ensure that rights and freedoms are safeguarded and the second is to ensure that the authority imposes order And what this means is that one cannot outweigh the other, In addition, the legislature had established legal and constitutional mechanisms to protect public freedoms and reduce abuse of power. As for the position of certain organic and procedural laws regarding the establishment of public freedoms in Algeria, s rights ", some laws have recognized this freedom and stipulate that they must be protected civilly and criminally from any assault not recognized by other laws and set out the framework for such protection in taking into account the balance between the interests of individuals and the interests of society, The legislator's restriction thus ensures such a balance. The study concluded with a series of conclusions and recommendations, the most important of which was to amend or add some legal texts, whether they relate to constitutional articles or articles of the Penal Code relating to the "protection of public freedoms". ............................. ملخص : انطلاقا من الفكرة التي يدور حولها موضوع البحث : النظام القانوني للحريات العامة في التشريع الجزائري ، يتضح لنا أن هنالك فكرة جوهرية يقوم عليها بحثنا ، ألا وهي المكانة القانونية والدستورية التي تحتلها الحريات العامة في الجزائر ، كما حرص الدستور الجزائري على أن يحقق التوازن بين أمرين ، الأمر الأول أن يكفل صيانة الحقوق والحريات والأمر الثاني أن يكفل للسلطة فرض النظام ، ومعنى هذا أنه لا يمكن تفوق أحدهما على الآخر ، إضافة إلى ذلك فإن المشرع وضع آليات قانونية وأخرى دستورية من أجل حماية الحريات العامة والحد من التعسف في استعمال السلطة . أمّا بالنسبة لموقف بعض القوانين العضوية والإجرائية بصدد إقرار الحريات العامة في الجزائر ، فقد اعترفت بعض القوانين بهذه الحرية ، كما نصّت على ضرورة حمايتها مدنيّا وجنائيا من أي اعتداء لم تعترف به قوانين أخرى ، وحددت إطار هذه الحماية في مراعاة الموازنة بين مصلحة الأفراد ومصلحة المجتمع ، ومن ثمة وضع المشرع من القيود ما يكفل هذه الموازنة . وانتهت الدراسة إلى مجموعة من النتائج والتوصيات وتتمثل أهمها في تعديل أو إضافة بعض النصوص القانونية سواء تعلق الأمر بمواد دستورية أو مواد في قانون العقوبات تتعلق بـ "حماية الحريات العامة" . .......................... Résumé de mémoire : A partir de l’idée autour de laquelle s’articule notre sujet de recherche : le système juridique des libertés publiques dans la législation algérienne. Notre recherche se base sur idée primordiale qui est la place importante accordée aux libertés publiques en Algérie . La constitution algérienne ville à maintenir l’équilibre entre le fait d’assurer les droits et les libertés d’une part et permettre aux autorités d’imposer l’ordre d’une autre . De plus le législateur a mis en œuvre des mécanismes juridiques et d’autres constitutionnels pour préserver les libertés et mettre fin à l’abus de pouvoir . Quant à la position de certaines lois constitutionnelles et procédurale qui adoptent les libertés publiques en Algérie , certaines lois ont reconnu cette liberté et prévoient la nécessité de sa préservation civile et pénale de tout empiétement , en assurant l’équilibre entre l’intérêt des individus et celui de la société . Notre étude est parvenue à un ensemble de constations et recommandations dont la plus importante est la modification ou l’ajout de quelques lois soi des articles constitutionnels ou des articles dans le code pénal qui concerne la préservation des libertés publiques .